Mechanistic aspects of the water-gas shift reaction on alumina-supported noble metal catalysts: in situ drifts and ssitka-mass spectrometry studies - Efstathiou, Angelos M.; Kalamaras, Christos M.; Olympiou, Georgios (My University, 2007)
Steady-state isotopic transient kinetic analysis (SSITKA) experiments coupled with mass spectrometry were performed for the first time to study essential mechanistic aspects of the water-gas shift (WGS) reaction over alumina-supported Pt, Pd, and Rh catalysts. In particular, the concentrations (μmol g-1) of active intermediate species found in the carbon-path from CO to the CO2 product gas (use of 13CO), and in the hydrogen-path from H2O to the H2 product gas (use of D2O) of the reaction mechanism were determined. It was found that by increasing the reaction temperature from 350 to 500 °C the concentration of active species in both the carbon-path and hydrogen-path increased significantly. Based on the large concentration of active species present in the hydrogen-path (OH/H located on the alumina support), the latter being larger than six equivalent monolayers based on the exposed noble metal surface area (θ > 6.0), the small concentration of OH groups along the periphery of metal-support interface, and the significantly smaller concentration (μmol g-1) of active species present in the carbon-path (adsorbed CO on the noble metal and COOH species on the alumina support and/or the metal-support interface), it might be suggested that diffusion of OH/H species on the alumina support towards catalytic sites present in the hydrogen-path of reaction mechanism might be considered as a slow reaction step. The formation of labile OH/H species is the result of dissociative chemisorption of water on the alumina support, where the role of noble metal is to activate the CO chemisorption and likely to promote formate decomposition into CO2 and H2 products. It was found that there is a good correlation between the surface concentration and binding energy of CO on the noble metal (Pt, Pd or Rh) with the activity of alumina-supported noble metal towards the WGS reaction.
Keywords: Water-gas; Chemisorption; Precious metals; Surface chemistry